EPISTEMOLOGI SUFI PERSPEKTIF AL-HAKIM AL-TIRMIDZI - Shah, M. Aunul Abied (Sekolah Tinggi Filsafat Islam (STFI) Sadra, 2012)
This article deals with some epistemological terms and theoretical postulates in the thought of a well known sufi from the 9th century AD., Abu `Abduâ€™lLah Muhammad b. `Ali al-Hakim al-Tirmidzi, in order to describe the path (sulÅ«k) of a sufi towards the Ultimate Reality. In his own style thought about the sufis, placing an emphasis upon the strong relations between the walÄyah (sufi sainthood) and the ma`rifa (sufi knowledge) in the one side, and between the two a philosophy of Sufi Ethics. So, it is nothing out of the ordinary to fi nd his ethical inclinations as a dominant feature in every aspect of his epistemological thoughts. In addition, sufi epistemology in the perspective of philosophers focuses on enforcing the inner positive potents of the Self more so than to eliminate â€œthe satanic infl uencesâ€ to the heart, because â€“ in al-Tirmidziâ€™s argument is that the former would greatly improve the immunity of the self, and encourage it to tread consistently on the right path as well.